Value of palliative gastrectomy in patients with stage IV gastric carcinoma - Duraker, Nüvit (Cerrahpaşa Medical Journal, 2014)
Objectives: The role of palliative gastrectomy in stage IV gastric carcinoma is controversial. In this study, the effect of palliative gastrectomy on the survival in patients with stage IV gastric carcinoma was investigated. Methods: One hundred eighty three stage IV gastric carcinoma patients who were followed-up until death were included in the study; data was collected prospectively. Patients with gastrectomy were compared to those without gastrectomy in regard to mortality and overall survival time; the patients who dead due to operative causes (30 patients) were not included in survival analysis. Results: Mortality ratio was 9.6% in patients with gastrectomy and 19.1% in patients without gastrectomy (p=0.181). Median survival time for 47 patients with gastrectomy (6.5 months) was significantly longer than 106 patients without resection (3.5 months) (p=0002); gastrectomy procedure had an independent prognostic significance (p<0.001). When the survival analysis was performed according to the extent of disease, the survival time was significantly longer in patients with gastrectomy than those without gastrectomy both in patients with locoregional disease (8 months versus 5 months; p=0.0343) and in patients with distant metastasis (6 months versus 2.5 months; p< 0.0001). Conclusion: Palliative gastrectomy should be performed in stage IV gastric carcinoma patients with good nutritional and general status since it does not have an increased mortality and provides a survival benefit, even for a short period of time, in comparison with nonresectional surgical procedures.